2020
DOI: 10.3329/bjb.v49i4.52517
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of walnut (Juglans regia L.) seedlings through SSR markers in north-western Himalayan region of Jammu

Abstract: screening of 25 SSR markers, revealed 23 clear and consistent amplification profiles in the entire walnut germplasm set. A total of 54 alleles were amplified by SSR primers and the number of alleles range from 2 to 3. The PIC value ranged from 0.36 to 0.68. The dendrogram classified all genotypes into two main clusters with various degrees of subclustering. Estimated genetic dissimilarity coefficient ranged from 0.36 to 0.85. Through model-based cluster analysis all genotypes were grouped into 5 genetically di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Structure analysis and cluster analysis indicated two groups of the apricot in the provinces of Jammu and Kashmir. The results reveal a significant correlation between genetic divergence and geographical distance ( He et al, 2007 , Shah et al, 2020 ). Two subpopulations revealed that sub-population-I had mostly exotic accessions, and sub-population-II contained indigenous genotypes with some of the genotypes found admixtures of these two subpopulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structure analysis and cluster analysis indicated two groups of the apricot in the provinces of Jammu and Kashmir. The results reveal a significant correlation between genetic divergence and geographical distance ( He et al, 2007 , Shah et al, 2020 ). Two subpopulations revealed that sub-population-I had mostly exotic accessions, and sub-population-II contained indigenous genotypes with some of the genotypes found admixtures of these two subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic markers are currently imperative for the analysis of diversity analysis and classification of plant germplasms with no environmental influence showing a high rate of reproducibility and efficiency. For evaluation of variability and genetic characterization of apricot and other stone fruits, numerous kinds of genetic markers have been employed, such as SSR, RAPD, AFLP, and RFLP ( Hormaza, 2002 , Hurtado et al, 2002 , Yilmaz et al, 2012 , Ballester and de-Vicente, 1998 , Wang et al, 2011 ; Shah et al, 2020 ). The low reproducibility of RAPD, high cost of AFLP and SSR primer’s development the sequence of flanking regions must be known are some limitations of these primers.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the variability and genetic characterization of apricot and other stone fruits, numerous kinds of genetic markers have been employed, such as SSR, RAPD, AFLP, and RFLP (Ballester and de-Vicente, 1998;Hurtado et al, 2002;Hormaza, 2002;Wang et al, 2011;Yilmaz et al, 2012;Shah et al, 2020). In apricot, RFLP and RAPD markers have been used to identify cultivars and to group them depending on their genetic similarity (Sheikh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been used effectively to characterize plants until today. Besides, molecular markers have been used to determine genetic diversity in walnuts, such as Random Amplified Polymorphic DNA (RAPD) (Nicese et al, 1998;;Sutyemez, 2006;Fatahi et al, 2010;Ahmed et al, 2012), Restriction Fragment Length Polymorphism (RFLP) (Fjellstrom et al, 1994;Potter et al, 2002;Kafkas et al, 2005), Inter-Simple Sequence Repeat (ISSR) (Potter et al, 2002;Pollegioni et al, 2003;Christopoulos et al, 2010;Li et al, 2011;Sutyemez et al, 2021), Amplified Fragment Length Polymorphism (AFLP) (Bayazit et al, 2007;Wang et al, 2011;Xu et al, 2012), Simple Sequence Repeats or microsatellites (SSR) (Dangl et al, 2005;Foroni et al, 2005;Victory et al, 2006;Wang et al, 2008;Chen et al, 2014;Vahdati et al, 2015;Bernard et al, 2018;Shah et al, 2020), and Single Nucleotide Polymorphism (SNP) (Bukucu et al, 2020a;Orman et al, 2020;Wang et al, 2020). With these techniques, walnut breeding studies have gained significant momentum.…”
Section: Introductionmentioning
confidence: 99%